Age, growth and natural mortality of coney (Cephalopholis fulva) from the southeastern United States - Burton, Michael L. (PeerJ, 2015)
Coney (Cephalopholis fulva) sampled from recreational and commercial vessels along the southeastern coast of the United States in 1998–2013 (n = 353) were aged by counting opaque bands on sectioned sagittal otoliths. Analysis of otolith edge type (opaque or translucent) revealed that annuli formed in January–June with a peak in April. Coney were aged up to 19 years, and the largest fish measured 430 mm in total length (TL). The weight-length relationship was ln(W) = 3.03 × ln(TL) − 18.05 (n = 487; coefficient of determination [r(2)] = 0.91), where W = whole weight in kilograms and and TL = total length in millimeters. Mean observed sizes at ages 1, 3, 5, 10, and 19 years were 225, 273, 307, 338, and 400 mm TL, respectively. The von Bertalanffy growth equation for coney was L(t) = 377 (1 − e((−0.20(t+3.53)))). Natural mortality (M) estimated by Hewitt and Hoenig’s longevity-based method which integrates all ages was 0.22. Age-specific M values, estimated with the method of Charnov and others, were 0.40, 0.30, 0.26, 0.22, and 0.20 for ages 1, 3, 5, 10, and 19, respectively.